2018
DOI: 10.1080/23746149.2017.1414631
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry demanded topological nodal-line materials

Abstract: The realization of Dirac and Weyl physics in solids has made topological materials one of the main focuses of condensed matter physics. Recently, the topic of topological nodal line semimetals, materials in which Dirac or Weyl-like crossings along special lines in momentum space create either a closed ring or line of degeneracies, rather than discrete points, has become a hot topic in topological quantum matter. Here, we review the experimentally confirmed and theoretically predicted topological nodal line sem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
157
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(177 citation statements)
references
References 168 publications
5
157
0
Order By: Relevance
“…In general, NLSMs without SOC will transform into either insulators, DSMs, WSMs or even double NLSMs when SOC is considered, which is much related to the symmetries in the corresponding systems. 56 While in this work, when SOC is included, the three nodal lines around Γ point will be gapped out with a small gap (≈ 5 meV), making YH 3 a topological insulator with Z 2 =(1,000). Nevertheless, further calculation shows that the gap induced by SOC along the nodal ring is very small (about 5 meV), which indicates that the effect of SOC is negligible and the characteristic of the nodal ring can be preserved.…”
Section: Introductionmentioning
confidence: 92%
“…In general, NLSMs without SOC will transform into either insulators, DSMs, WSMs or even double NLSMs when SOC is considered, which is much related to the symmetries in the corresponding systems. 56 While in this work, when SOC is included, the three nodal lines around Γ point will be gapped out with a small gap (≈ 5 meV), making YH 3 a topological insulator with Z 2 =(1,000). Nevertheless, further calculation shows that the gap induced by SOC along the nodal ring is very small (about 5 meV), which indicates that the effect of SOC is negligible and the characteristic of the nodal ring can be preserved.…”
Section: Introductionmentioning
confidence: 92%
“…24 We should mention that CaAgAs and CaAgP have been predicted to be NLSMs as well, 21 and although the electronic structure has not yet been confirmed, some typical transport phenomena have been observed in CaAgAs. 107 NLSMs have recently been reviewed by Ali et al 105 and thus we refer the reader to this reference for further detailed descriptions of the crystal and electronic structures of these materials.…”
Section: Weyl Semimetalsmentioning
confidence: 99%
“…It has been reported that the Weyl nodes can occur at points other than high symmetry k-path unlike nodal line semimetals. 18,20 Type I Weyl points cause point-like Fermi surface (FS) and hence difficult to identify. However, 2D band structure of tilted Dirac cone causes the crossed Fermi lines (see Fig.1(g)) centred at Weyl node.…”
mentioning
confidence: 99%